2012
DOI: 10.5897/ajb11.3331
|View full text |Cite
|
Sign up to set email alerts
|

In planta transformation of rice (Oryza sativa) using thaumatin-like protein gene for enhancing resistance to sheath blight

Abstract: Among the fungal diseases, sheath blight caused by Rhizoctonia solani Kuhn is one of the most important wide spread diseases found in all the rice plants (Oryza sativa) growing countries. The control of the disease with agricultural alternation and traditional breeding has not been successful so far. Application of fungicide is not recommended. Resistant genes which can cause immunity to the disease have not been found. D34 is a thaumatin-like protein (TLP) belonging to the group 5 of pathogen-related proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
2
5
0
1
Order By: Relevance
“…In the presence of 100 lM acetosyringone, 32.6 % of Agrobacterium-infected setts were sprouted in 30 mg l -1 BASTA Ò solution, reaching a transformation efficiency of 11.6 % ( Table 2). A similar improvement of transformation with acetosyringone was reported in switchgrass, rice, Medicago truncatula, Arabidopsis, and cowpea (Chen et al 2010;Naseri et al 2012;Trieu et al 2000;Li et al 2009b;Adesoye et al 2010). Application of acetosyringone, above 100 lM reduced sett sprouting ability, which ultimately led to a lower transformation efficiency (Table 2).…”
Section: Influence Of Different Agrobacterium Strains and Acetosyringsupporting
confidence: 65%
“…In the presence of 100 lM acetosyringone, 32.6 % of Agrobacterium-infected setts were sprouted in 30 mg l -1 BASTA Ò solution, reaching a transformation efficiency of 11.6 % ( Table 2). A similar improvement of transformation with acetosyringone was reported in switchgrass, rice, Medicago truncatula, Arabidopsis, and cowpea (Chen et al 2010;Naseri et al 2012;Trieu et al 2000;Li et al 2009b;Adesoye et al 2010). Application of acetosyringone, above 100 lM reduced sett sprouting ability, which ultimately led to a lower transformation efficiency (Table 2).…”
Section: Influence Of Different Agrobacterium Strains and Acetosyringsupporting
confidence: 65%
“…Keshamma et al (2008) also reported transformation frequency of 8.3% to 19% in cotton by employing the same method with a slight variation in colonization period as 60 min instead of 15 min used in the present investigation. Similar technique giving transformation frequencies of 24% and 9% were also reported in rice by Naseri et al (2012) and Allahi et al (2014) by the same injection method, but without colonization. Several other reports are in close conformity with these results viz.…”
Section: Recovery Of Putative Transgenics and Transformation Frequencysupporting
confidence: 70%
“…[76, 77], Colletotrichum gloeosporioides [78], Fusarium sp . [79], Podosphaera xanthii [57], Rhizoctonia solani [45, 80], Sclerotinia sclerotiorum [81], Verticillium dahliae [68] etc. The results of expression analysis of studied five cereals suggest the putative roles of TLPs in various abiotic and biotic stress conditions.…”
Section: Discussionmentioning
confidence: 99%